Utilizing P7 as a Model to Facilitate Language Teacher Development Program: Implication for Applied Linguistics - Muhammad-Gombe, Umar; Gbeyonron, Clifford Irikefe; Iorember, Margaret N. (Indonesian Journal of English Language Studies (IJELS), 2024)
This research focuses on the imperative need for effective language teacher production in Nigeria to meet the growing demand for language education and applied linguistics. The study introduces the P7 Model, a comprehensive framework that encompasses seven key elements essential for successful language teacher development: Personnel, Potentials, Partnership, Process, Property, Product, and Probing. The research involves a survey of 400 practicing language teachers across various educational levels in Nigeria. The survey examines their perceptions regarding the importance of these seven elements in shaping language teacher education programs. The findings are analyzed using simple percentages. The results highlight strong agreement among respondents concerning the significance of each P7 element in the language teacher development process. Specifically, participants emphasize the need for competent, proficient, and enthusiastic teaching staff (Personnel), collaborative efforts through partnerships, research, and engagement with regulatory bodies (Partnership), admission of candidates with a genuine interest in language teaching and strong academic potential (Potentials), a curriculum emphasizing practical skills and employability (Process), the provision and optimal use of infrastructure and resources (Property), job security, remuneration, incentives, and continuing professional development (Product), and quality assurance and control throughout the teacher development process (Probing). The P7 Model offers a structured approach to guide language program administrators and policymakers in shaping effective language teacher education programs. Prioritizing these elements is crucial to ensure the availability of skilled, dedicated, and enthusiastic language teachers who can meet the demands of the 21st century, ultimately facilitating applied linguistics and language education in Nigeria.